Hondurodendron, a new monotypic genus of Aptandraceae from Honduras. - KELLY, DANIEL LUCIUS (My University, 2010)
Hondurodendron C. Ulloa, Nickrent, Whitef. & D. Kelly, a new monotypic genus endemic to Honduras, is here described and illustrated. The new species, H. urceolatum C. Ulloa, Nickrent, Whitef. & D. Kelly, is a dioecious tree, distinguished by its minute flowers borne on densely tomentose inflorescences, unique anthers opening by three valves, and a characteristic fruit totally enveloped by the accrescent calyx, which projects beyond the fruit. A molecular analysis based on four genes (nuclear small subunit [SSU] ribosomal DNA [rDNA], chloroplast rbcL, matK, and accD) placed this genus in a clade with Aptandra Miers, Harmandia Pierre ex Baill., Chaunochiton Benth., and Ongokea Pierre in the family Aptandraceae Miers. Resumen: Se describe e ilustra un nuevo genero monotipico Hondurodendron C. Ulloa, Nickrent, Whitef. & D. Kelly endemico de Honduras. La nueva especie H. urceolatum C. Ulloa, Nickrent, Whitef. & D. Kelly es un arbol dioico, que se distingue por las flores diminutas en inflorescencias densamente tomentosas, las anteras unicas que se abren por tres valvas y un fruto caracteristico totalmente encerrado por el caliz acrescente que se proyecta sobre este. Un analisis molecular con cuatro genes (SSU ADN ribosomico nuclear, rbcL del cloroplasto, matK y accD) ubica al genero en un clado junto con Aptandra Miers, Harmandia Pierre ex Baill., Chaunochiton Benth. y Ongokea Pierre en la familia Aptandraceae Miers.
PUBLISHED
Keywords: Botany; Hondurodendron